Neighborhoods and Racial Inequality in Assortative Mating and Fertility in the United States - Karl Vachuska (Societies)
While racial inequalities in assortative mating and fertility have been well documented, the role of neighborhoods has frequently been overlooked in explaining these disparities. In this study, I use restricted birth record data from the state of California with neighborhood-level socioeconomic and demographic data to explore the roles of neighborhoods and structural neighborhood inequality in mediating racial inequality in assortative mating and fertility in 2018 and 2019. Overall, neighborhood disadvantage, particularly disadvantage measured in a neighborhood’s mobility network, mediated a substantial proportion of the disparity in fathers’ educational attainment between White and Black or Hispanic mothers in California in 2018 and 2019. Additionally, while I observe evidence of Black and Hispanic neighborhoods having significantly greater fertility rates than White neighborhoods, this gap can be entirely explained by neighborhood disadvantage. Lastly, a significant share of the fertility gap between less-educated White and Black women is mediated by neighborhood disadvantage. This study motivates more research at the intersection of assortative mating and fertility at the neighborhood scale.